Q. 45.0( 1 Vote )

# Evaluate: Let Putting Which implies,

A(x-2)(x-4)+Bx(x-4)+Cx(x-2)=1

Now put x-2=0

Therefore, x=2

A(0)+B×2(2-4)+C(0)=1

B×2(-2)=1 Now put x-4=0

Therefore, x=4

A(0)+B×(0)+C×4(4-2)=1

C×4(2)=1 Now put x=0

A(0-2)(0-4)+B(0)+C(0)=1 Now From equation (1) we get   Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos  Lecture on integration by partial fractions62 mins  Fundamental Integration Formula59 mins  Lecture on Integration by parts55 mins  Integration by Substitution56 mins  Interactive Quiz on Integration by Substitution47 mins  Definite Integration | Ready for a quiz?FREE Class  Differentiability by using first principle59 mins  Lecture on some forms of integration54 mins  Interactive Quiz | Differentiability by using first principle59 mins  Interactive Quiz on Integration by Parts56 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses 